1990
DOI: 10.1007/bf01183986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium in freshwater clams. II. Ultrastructural changes in the renal system ofAnodonta cygnea

Abstract: An ultrastructural study was made of the renal system of freshwater clams,Anodonta cygnea, that had been exposed to cadmium chloride (50 μg Cd/L) for 12 weeks. By stereological analysis an extended lysosomal system and a decreased number of mitochondria was apparent in the epithelial cells lining the proximal compartment of the kidney. The increase of the lysosomal system was mainly accountable to the appearance of a distinct type of lysosome, that accumulated in the apical cell region. The decrease of the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…After 24h of metaldehyde treatment, remarkable increase in the number and size of concretions in the kidney epithelium was observed compared to that of control snails. The same effect has been observed in the kidney of bivalves under heavy metal stress (Sulina, 1986(Sulina, , 1989Hemelraad et al, 1990 andRegoli et al, 1992). Also, non metal organic pollutants caused an increase in the number of concretions in the kidneys of the marine prosobranch Littorina littorea and in the freshwater snail Planorbarius corneus (Klobučar et al, 2001).…”
Section: (A) a Continuous Epithelium Of Columnar Cells The Nephrocytsupporting
confidence: 59%
“…After 24h of metaldehyde treatment, remarkable increase in the number and size of concretions in the kidney epithelium was observed compared to that of control snails. The same effect has been observed in the kidney of bivalves under heavy metal stress (Sulina, 1986(Sulina, , 1989Hemelraad et al, 1990 andRegoli et al, 1992). Also, non metal organic pollutants caused an increase in the number of concretions in the kidneys of the marine prosobranch Littorina littorea and in the freshwater snail Planorbarius corneus (Klobučar et al, 2001).…”
Section: (A) a Continuous Epithelium Of Columnar Cells The Nephrocytsupporting
confidence: 59%
“…An increase is evident in all measurements used (N ca , A ca , A ec ). Up to now, this kind of event has been mostly associated with heavy metal exposure (Sunila 1986, 1989, BallanDufrancais et al 1990, Hemelraad et al 1990, Hyne et al 1992, Giamberini et al 1996 although one can find work concerning toxic effects of non metals on molluscan kidney (Cajaraville et al 1990).…”
Section: Light Microscopical Analysis Of the Pcp-exposedmentioning
confidence: 99%
“…Their histopathological analysis provides information about the general health of the animals and contaminant-specific changes in the tissues. Although laboratory as well as field studies suggest that pollutants cause toxic effects to molluscs, the histopathological effects of chemical contaminants have not generally been measured (Sunila 1986, 1989, Hemelraad 1990, Marigómez 1990a. When measured, different qualitative, semi-quantitative, and quantitative approaches were used (Lowe 1988, Cajaraville 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Adult lamellibranchs utilize carbohydrates rather than lipids as a major energy reserve (Holland and Spencer 1973). Hemelraad et al (1990b) Hameed and Raj (1989) reported dissolution of the crystalline style for the freshwater bivalve Lamellidens marginalis (adults) following exposure to sublethal concentrations of cadmium (11 mg/L), copper (9.75 mg/L) and mercury (6.5 mg/L). Dissolution times ranged from 18 minutes for copper and cadmium to 24 minutes for mercury.…”
Section: Effects On Lipid Catabolismmentioning
confidence: 99%
“…Adult mussels have been used in a wide variety of contaminant studies, including biomonitoring, bioaccumulation, lethality and histopathology studies Henwig et al 1989;Hemelraad et al 1990aHemelraad et al , 1990bHemelraad et al , 1990c; whereas juveniles have been used almost exclusively In lethality studies . Until recently, studies with young unionid freshwater juveniles were difficult to conduct because of their small size at metamorphosis (approximately 90-400 ^m in length) and problems associated with maintaining and rearing juveniles In the laboratory.…”
Section: Introductionmentioning
confidence: 99%